Triatoma rubrovaria (Hemiptera, Reduviidae, Triatominae) in the Pampa biome, Brazil: a retrospective study of its occurrence and abundance - Souza, Cassiane Borges de; Santos, Gabriel Borges dos; Bedin, Cleonara; Bergamin, Marcelo; Mello, Fernanda de; Villela, Marcos Marreiro (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Triatoma rubrovaria has been captured in some areas of Rio Grande do Sul State (RS), Brazil, as this species can be found in the Pampa biome. Its distribution across this biome should be described in detail to verify the potential of this vector to transmit Trypanosoma cruzi. This study aimed to investigate the occurrence of T. rubrovaria in the Pampa biome and transitional areas of RS. The collected information resulted from the analysis of secondary data provided by the Centro Estadual de Vigilancia em Saude (CEVS – State’s Center of Health Surveillance). The following aspects were taken into consideration: the year in which the insect was captured, the city, the number of specimens captured, invasion or domiciliation, the notification in the household, surroundings or both, and T. cruzi infection. The data comprised the period from 2009 to 2020, in 109 cities located in the Pampa biome and 98 located in transitional areas. The Pampa biome exhibited 85% of the occurrences of T. rubrovaria, while 1.2% of specimens were T. cruzi-like positive. Both the first and second biennia concentrated 64.6% of captures. Alegrete city, Cangucu city and Piratini city were the locations in the Pampa where the largest numbers of specimens were found. Regarding the transitional areas, Roque Gonzales city, Santiago city and Santana da Boa Vista city exhibited the largest numbers. Most insects were adults, which were found in households. Even though positivity for T. cruzi-like was low, the species still has epidemiological importance in the region.